CHANGES OF SEXUAL ACTIVITIES IN MENOPAUSAL WOMEN IN RW 005 KELURAHAN PARIGI BARU PONDOK AREN TANGERANG SELATAN IN 2020 - Suzanna Fabella Putri; Maya Anggraeni; Dewi Anggraini (Jurnal Kesehatan STIKes IMC Bintaro, 2020)
Sexuality in menopausal women experiences various changes including physical and psychological changes. Psychological complaints that occur in menopausal women are sleep disorders, anxiety, irritability, stress, depression and anxiety. Changes in sexual activity can be characterized by physical complaints, which include hot flushes, decreased bone density, decreased skin elasticity, thinning of the vaginal wall and vaginal dryness that can cause pain during intercourse. This study aims to determine changes in sexual activity in mmum menopause period of 1 year obtained through purposive sampling. The results of this study describe four themes, namely: the first theme, changes in sexual interest and frequency of sexual relations, the second theme of factors affecting senopausal women. This study uses descriptive qualitative phenomonology methods with in-depth interviews. Participants in this study were 10 people with age 45 years and above with a miniexual relations including partners, partner response, and psychological factors, the third theme of myths in menopausal women, the fourth theme, the hopes of the wife and husband after the wife experiences menopause. The conclusion of this study is that there are changes in sexual activity in menopausal women in terms of the factors that influence menopause. Suggestions from this study are needed for health education, guidance and counseling about sex so that people know about the changes that occur after menopause.